The Effect Of Learning Organizational Culture, Academic Leadership And Collegiality Climate On Knowledge Sharing Behavior In Educational Institutions - Firman Aziz; Hadi Prayitno; Samuel Aditya Eko Putranto; Basuki Wisnu; Fatimah Malini Lubis; Apriani Riyanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The core intent of this research is to find out the roles that the learning organizational culture, academic leadership, and collegiality contribute to the knowledge-sharing behavior development in educational institutions. The research issue is set on the proposition that knowledge sharing has a good effect on learning and academic performance. An explanatory quantitative design was employed in the study that consisted of 160 educators who were selected by purposive sampling. The data collection instrument was a five-point Likert scale questionnaire, and the data were analyzed using multiple linear regression. The findings show that learning organizational culture, academic leadership, and collegiality are not only the factors but also the main contributors to the knowledge-sharing behavior, which is the most significant and positive impact. This research, on the one hand, significantly contributes to the theory of educational management and organizational behavior in the context of learning organizations and on the other hand, provides educational institutions with strategic implications through the continuous interaction of learning culture, collaborative academic leadership, and collegial work climate.